RANCANGAN SISTEM INFORMASI DATA PERSEDIAAN BARANG WASERDA PADA KUD MUKTI TAMA SUNGAI BAHAR IV KABUPATEN MUARO JAMBI - Sri Mulyati (JURNAL AKADEMIKA)
Computers at the present time this is no longer a strange and expensive, at present almost all fields require a computer as a tool because it has the advantages in terms of accuracy and speed. For example in the field of health, engineering, civil, banking, science, and business services sector by both government and private. Advantages and benefits that can be obtained if a bookkeeping process is done by using computer systems as a tool to carry out the work process a lot. For example, the computer system can generate information more quickly than the simple application because the computer can execute several programs at the same time. By using a computer then this will reduce and even eliminate the mistakes, this is because the level of computer accuracy is much higher than human accuracy. In addition, the computer is also equipped with a variety of ways to prevent mistakes so that the systemadministration office or the company could do a quick report and perform many other processes are certainly not independent of human involvement in operation and can print reports that are used within the company.